A computational framework for coating fatigue analysis of wind turbine blades due to rain erosion. (June 2021) - Hu, Weifei; Chen, Weiyi; Wang, Xiaobo; Jiang, Zhiyu; Wang, Yeqing; Verma, Amrit Shankar; Teuwen, Julie J.E.
Abstract: The rain-induced fatigue damage in the wind turbine blade coating has attracted increasing attention owing to significant repair and maintenance costs. The present paper develops an improved computational framework for analyzing the wind turbine blade coating fatigue induced by rain erosion. The paper first presents an extended stochastic rain field simulation model that considers different raindrop shapes (spherical, flat, and spindle), raindrop sizes, impact angles, and impact speeds. The influence of these raindrop characteristics on the impact stress of the blade coating is investigated by a smoothed particle hydrodynamics approach. To address the expensive computational time, a stress interpolation method is proposed to calculate the impact stress of all raindrops in a random rain event. Furthermore, coating fatigue analysis is performed by including the fatigue crack initiation in the incubation period and the fatigue crack propagation in the mass-loss-rate increasing period due to raindrop impact. Finally, the proposed computational framework is verified by comparing the estimated fatigue life with those obtained in literature. The results from the study show that by incorporating the statistics of rainfall data, the proposed framework could be used to calculate the expected fatigue life of the blade coating due to rain erosion. Highlights: Rain field simulation considers varied raindrop shapes, sizes, and distributions. Raindrop impact stress is calculated based on smooth particle hydrodynamics. Rain erosion of blade coating includes fatigue incubation and increasing periods.